Postpartum Thyroiditis: A Case Report - Pangaribuan, Jessica Patricia; Santi Syafril (TALENTA Publisher, Universitas Sumatera Utara, 2021)
ABSTRACT: Background: Postpartum thyroiditis (PPT) is a thyroid dysfunctionn syndrome which is temporary or permanent that occurs 1 year after giving birth or abortion. The occurrence of postpartum thyroiditis is 5 – 10% of postpartum women in the world. It is caused by an inflammation of the thyroid gland which leads to a destruction of the thyroid follicle and proteolysis of thyroglobulin. Case presentation: A woman, 31 years old, was admitted to the hospital complaining an enlargement on her neck. The patient said her the enlargement keeps getting larger and she also complained a feeling of something stuck in the throat. The patient also complained a hoarse voice. The patient has just given birth of her second child 5 months ago. From a hematologic examination, radiologic, and blood culture, the patient was diagnosed with Postpartum Thyroiditis. The patient was given Euthyrox therapy and will undergo repeated evaluation after 1 months of the therapy. Conclusion: We reported a case of Postpartum Thyroiditis that was treated comprehensively, and showed a good prognosis.